Design and construction of a proportional gas flow meter with application in Mössbauer spectroscopy - Marín Ramirez, Juan Marcos; Cáceres Díaz, Luis Alberto; Rojas Martínez, Yebrail Antonio; Osorio Vélez, Jaime Alberto; Medina Barreto, Milton Humberto; Cruz Muñoz, Beatriz (Scientia et Technica, 2018)
The design, construction and operation parameters of a gas flow proportional counter are presented in order to implement the integral conversion electron mössbauer spectroscopy technique (ICEMS). The detector works with the support of a multi-channel detection system and a source of highenergy radiation of 57Co. A constant gas flow of a mixture of 5% CH4 in He was used as a multiplier gas, which increased the signal intensity, and protected the sample´s surface of electric shocks. An internal filter for low energy X-rays was considered during the design to achieve a lower background noise and optimize the volume of gas consumed. With this built-in ICEMS detector it is feasible to characterize efficiently the magnetic properties and oxidation states (hyperfine interactions) of both bulk materials and thin films. The calibration of the device was performed by using an iron sample synthesized by powder metallurgy. It was successfully identified the presence of a distinctive sextet of the α-Fe phase with a hyperfine field of 330 kOe and an isomer shift of 0.312 mm / s. The great usefulness of the equipment was verified by solving the magnetic hyperfine interactions of the Mössbauer spectrum associated to a commercial stainless-steel washer.